Correlation between clinical findings and patient’s survival rate in congenital duodenal obstruction - Chandra Adipurwadi; Akhmad Makhmudi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Congenital duodenal obstruction (CDO) is one of the most common anomalies in newborns (0-30 days), and accounting for nearly half of all cases of neonatal intestinal obstruction. Although survival in infants with congenital intestinal obstruction has improved, duodenal obstruction continues to present unique challenges. A retrospective correlational study was used in this study, 49 patients with CDO were analyzed within the years of 2004 to 2009. A chi-square test was used to investigate the correlation between clinical findings (age, weight, gestational age, surgical techniques, comorbidity, and early enteral feeding) and patient’s survival rate. None of clinical findings showed a significant correlation with patient’s survival rate, except comorbidity (sepsis) and early enteral feeding showed a significant correlation with patient’s survival rate (p<0.05). In conclusion, this study revealed that comorbidity (sepsis) and early internal feeding correlated with patients’ survival rate.